Engraftment of Transplanted Buccal Epithelial Cells onto the Urethrotomy Site, Proven Immunohistochemically in Rabbit Model; a Feat to Prevent Urethral Stricture Recurrence - Akio Horiguchi; Masayuki Shinchi; Kenichiro Ojima; Yusuke Hirano; Toshihiro Kushibiki; Yoshine Mayumi; Kosuke Miyai; Ichiro Miura; Masaru Iwasaki; Vaddi Suryaprakash; Rajappa Senthilkumar; Senthilkumar Preethy; et al. (Stem Cell Reviews and Reports, 2023)

A novel human donor cornea preservation cocktail incorporating a thermo-reversible gelation polymer (TGP), enhancing the corneal endothelial cell density maintenance and explant culture of corneal limbal cells - Bhuvaneshwari Namitha; Munusamy Rajendran Chitra; Mathevan Bhavya; Periasamy Parikumar; Shojiro Katoh; Hiroshi Yoshioka; Masaru Iwasaki; Rajappa Senthilkumar; Mathaiyan Rajmohan; Ramalingam Karthick; Senthilkumar Preethy; Samuel J. K. Abraham (Biotechnology Letters, 2021)
Purpose McCarey-Kaufman’s (MK) medium and Optisol-GS medium are the most commonly employed media for human donor corneal preservation. In this study, we evaluated the preservation efficacy of discarded human donor corneas using a Thermo-reversible gelation polymer (TGP) added to these two media. Methods Thirteen human corneal buttons collected from deceased donors, which were otherwise discarded due to low endothelial cell density (ECD) were used. They were stored in four groups: MK medium, MK medium with TGP, Optisol-GS and Optisol-GS with TGP at 4 °C for 96 h. Slit lamp examination and specular microscopy were performed. Corneal limbal tissues from these corneas were then cultured using explant methodology one with and the other without TGP scaffold, for 21 days. Results MK + TGP and Optisol-GS + TGP preserved corneas better than without TGP, which was observed by maintenance of ECD which was significantly higher in Optisol-GS + TGP than MK + TGP (p-value = 0.000478) and corneal thickness remaining the same for 96 h. Viable corneal epithelial cells could be grown from the corneas stored only in MK + TGP and Optisol-GS + TGP. During culture, the TGP scaffold helped maintain the native epithelial phenotype and progenitor/stem cell growth was confirmed by RT-PCR characterization. Conclusion TGP reconstituted with MK and Optisol—GS media yields better preservation of human corneal buttons in terms of relatively higher ECD maintenance and better in vitro culture outcome of corneal limbal tissue. This method has the potential to become a standard donor corneal transportation-preservation methodology and it can also be extended to other tissue or organ transportation upon further validation.